Application of MS-ICHOA in large scale cascade hydropower stations operation optimization and research on corresponding water storage and release rules - Yang, Peiyao; Jiang, Zhiqiang; Qin, Hui; Zhang, Yongchuan; Xiao, Wenjing; Liu, Gang (Energy (Oxford), 2025)
To further accurate test the applicability of previously proposed improved chimp optimization algorithm integrating multiple strategies (MS-ICHOA) in the large-scale reservoirs optimization and enrich the content of water storage and release, the optimal operation issue of six giant cascade reservoirs in the lower Jinsha River to the upper Yangtze River is tackled. The comparison results with advanced algorithms and the statistical storage and release rules show that, for inflows of ultra-wet, relatively wet, normal, relatively dry and ultra-dry, MS-ICHOA can reduce water spillage, increase power generation and demonstrate strong robustness compared to contrast methods. Actual operation can be proceeded according to the storage sequence of Baihetan, Wudongde, Xiluodu, Xiangjiaba and Three Gorges, as well as the release sequence of Wudongde, Baihetan, Three Gorges, Xiluodu and Xiangjiaba. Wudongde, Baihetan, Xiluodu, Xiangjiaba and Three Gorges can respectively accelerate storage rates in the 23rd-24th, 21st-24th, 24th-25th and 27th-28th, 26th and 29th, and 27th-28th ten-day, can respectively increase the release progress at the 7th-9th, 10th-13th, 16th, 17th, and 15th ten-day. For inflows between ultra-wet and relatively dry, under the same constraints and boundaries, MS-ICHOA can make the total power generation during release period increase by 9.83 %–20.12 % compared to the best-performing ALO among comparison methods. •Established a complex optimization operation model for large-scale cascade reservoirs.•MS-ICHOA outperforms other algorithms in statistical analysis and scheduling process.•Summarized the water storage and release laws (order and time) of cascade reservoirs.•MS-ICHOA can improve the cascade total power generation during the release period.